2020
DOI: 10.1186/s40478-020-00924-7
|View full text |Cite
|
Sign up to set email alerts
|

Biological links between traumatic brain injury and Parkinson’s disease

Abstract: Parkinson's Disease (PD) is a progressive neurodegenerative disorder with no cure. Clinical presentation is characterized by postural instability, resting tremors, and gait problems that result from progressive loss of A9 dopaminergic neurons in the substantia nigra pars compacta. Traumatic brain injury (TBI) has been implicated as a risk factor for several neurodegenerative diseases, but the strongest evidence is linked to development of PD. Mild TBI (mTBI), is the most common and is defined by minimal, if an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(73 citation statements)
references
References 168 publications
(203 reference statements)
4
69
0
Order By: Relevance
“…An increasing number of epidemiological studies have implicated TBI as a major non-genetic risk factor for later development of neurodegenerative disease ( Delic et al, 2020 ), with the strongest evidence associated with PD ( Crane et al, 2016 ; Gardner et al, 2018 ). In the light of studies demonstrating the aberrant overexpression of α-synuclein coincident with neuroinflammation in brain following TBI, and suggesting α-synuclein as key a pathological link between TBI and later development of PD-like symptoms in humans and animal models of TBI ( Acosta et al, 2015 ; Wong and Hazrati, 2013 ), we evaluated whether DP and Pom could mitigate α-synuclein-induced toxicity in primary neuronal cultures containing dopaminergic neurons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of epidemiological studies have implicated TBI as a major non-genetic risk factor for later development of neurodegenerative disease ( Delic et al, 2020 ), with the strongest evidence associated with PD ( Crane et al, 2016 ; Gardner et al, 2018 ). In the light of studies demonstrating the aberrant overexpression of α-synuclein coincident with neuroinflammation in brain following TBI, and suggesting α-synuclein as key a pathological link between TBI and later development of PD-like symptoms in humans and animal models of TBI ( Acosta et al, 2015 ; Wong and Hazrati, 2013 ), we evaluated whether DP and Pom could mitigate α-synuclein-induced toxicity in primary neuronal cultures containing dopaminergic neurons.…”
Section: Resultsmentioning
confidence: 99%
“…Beyond the short-term consequences of neuronal dysfunction and loss induced by TBI, biochemical cascades are initiated that can lead to an increased risk of neurodegenerative disorders and, in particular, PD ( Delic et al, 2020 ; Gardner et al, 2018 ; Crane et al, 2016 ). α-Synuclein has been proposed as the key pathological link between the chronic effects of TBI and later development of PD ( Acosta et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic brain injury (TBI) is a global risk factor and the leading cause of neurological disability. Recent studies have reported that TBI is associated with several neurodegenerative diseases, such as Alzheimer’s and Parkinson’s disease [ 1 , 2 , 3 ]. TBI leads to a primary injury, which is followed by a secondary brain injury.…”
Section: Introductionmentioning
confidence: 99%
“…Insomnia-associated cognitive decline is associated iron accumulation, oxidative stress, and inflammation [ 73 ], and may likewise be ameliorated with IN DFO treatment. Furthermore, accumulation of iron is thought to be one of the many pathophysiological sequelae of traumatic brain injury (TBI) [ 125 ]. DFO has been shown to suppress this post-TBI iron overload as well as reverse hydrocephalus and cognitive deficits following TBI in animal models [ 79 , 126 , 127 , 128 ].…”
Section: In Dfo For Other Neurological Diseasesmentioning
confidence: 99%
“…DFO has been shown to suppress this post-TBI iron overload as well as reverse hydrocephalus and cognitive deficits following TBI in animal models [ 79 , 126 , 127 , 128 ]. The sequelae of TBI combine neurodegenerative, neuroinflammatory, and both ischemic and hemorrhagic neurovascular components [ 125 ], a perfect model wherein DFO may uniquely enact beneficial impact through its multiple intersecting disease-modifying mechanisms.…”
Section: In Dfo For Other Neurological Diseasesmentioning
confidence: 99%